Stress Perception, Smoking and Drinking Behaviors among Adolescents - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study aimed to examine the relationship between stress perception and smoking and drinking behaviors among adolescents in one region of South Korea. Data were collected online from elementary, middle, and high school students. This study found that smokers had higher stress perception scores than nonsmokers (t=-8.100, p<0.001), and drinkers had higher stress perception scores than nonsmokers (t=8.380, p<0.001). The major factors for stress were grade or career, appearance, and conflict with parents, friends, seniors, and juniors. It is necessary to identify the differences in stress caused by smoking and drinking among adolescents in a community and understand the causes of stress so that they can manage their stress on their own.